Implementasi Peraturan Menteri Dalam Negeri Nomor 3 Tahun 2024 dalam Penyelesaian Pengadaan Tanah Kas Desa untuk Pembangunan Bendungan Karangnongko di Kabupaten Bojonegoro - randidwi wantoro; Eko Suharto (Tunas Agraria, 2026)
Abstract: Karangnongko Dam construction in Bojonegoro Regency involves Village Treasury Land (TKD) in Kalangan and Ngelo Villages. TKD acquisition is governed simultaneously by land-acquisition law and village-asset management law, so payment of compensation does not automatically restore village assets. This article analyzes TKD compensation, identifies social, administrative, juridical, and institutional constraints, and examines the implementation of Minister of Home Affairs Regulation Number 3 of 2024. Using a qualitative case-study method, data were collected through interviews with 28 informants, field observation, and document analysis. Interview data were coded through open coding, thematic categorization, and theory-based coding using implementation gap, Edward III, and legal pluralism as the main analytical framework. The findings show that formal land-acquisition stages have been implemented, including location determination, inventory, appraisal, deliberation, and payment. However, substantive completion has not been achieved because replacement land has not yet been fully acquired, certified, recorded, and restored as village assets. The main bottleneck has shifted from pre-payment legality to post-payment governance, including blocked accounts, operational costs, appraisal of replacement land, tiered approvals, treatment of bank interest, and weak inter-agency coordination. The article contributes to the literature by shifting the success indicator of TKD acquisition from compensation payment toward village-asset recovery. Keywords: Karangnongko Dam, Land Acquisition, Minister of Home Affairs Regulation Number 3 of 2024, Policy Implementation, Village Treasury Land   Abstrak: Pengadaan Tanah Kas Desa (TKD) untuk pembangunan Bendungan Karangnongko di Kabupaten Bojonegoro berada pada irisan rezim pengadaan tanah dan rezim pengelolaan aset desa. Penelitian ini menganalisis pelaksanaan ganti rugi TKD, mengidentifikasi kendala sosial, administratif, yuridis, dan kelembagaan, serta mengkaji implementasi Permendagri Nomor 3 Tahun 2024 di Desa Kalangan dan Desa Ngelo. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus melalui wawancara terhadap 28 informan, observasi lapangan, dan studi dokumen. Data wawancara dianalisis melalui coding terbuka, kategorisasi tematik, dan coding berbasis kerangka implementation gap, Edward III, dan legal pluralism. Hasil penelitian menunjukkan bahwa tahapan formal pengadaan tanah telah dilaksanakan, meliputi penetapan lokasi, inventarisasi, penilaian, musyawarah, dan pembayaran ganti kerugian. Namun, penyelesaian substantif belum tercapai karena tanah pengganti belum sepenuhnya diperoleh, disertipikatkan, dicatat, dan dipulihkan sebagai aset desa. Hambatan utama bergeser dari legalitas prapembayaran menuju tata kelola pascapembayaran, seperti rekening khusus yang diblokir, kebutuhan biaya operasional, appraisal tanah pengganti, perizinan berjenjang, perlakuan bunga rekening, dan koordinasi antarinstansi yang belum terlembaga. Kontribusi artikel ini adalah menggeser ukuran keberhasilan pengadaan TKD dari indikator pembayaran ganti kerugian menuju indikator pemulihan aset desa. Kata Kunci: Bendungan Karangnongko, Implementasi Kebijakan, Pengadaan Tanah, Permendagri Nomor 3 Tahun 2024, Tanah Kas Desa